Flip a coin or vote: An Experiment on Choosing Group Decision Rules - Timo Hoffmann; Sander Renes (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Before a group can take a decision, its members must agree on a mechanism to aggregate individual preferences. In this paper we present the results of an experiment on the influence of private payoff information and the role of the available alternatives on individuals' mechanism choices in such group choice situations. While efficient mechanisms are desirable, we experimentally show that participation constraints can prevent their implementation. We find strong indications that individual preferences for choice rules are sensitive to individual expected payoffs. Our results highlight the importance of considering participation constraints when designing choice institutions.
Keywords: C91; D70; D82; 330